Complete cat care - Atkinson, Sam (DK Publishing, 2014)
"Combining everything you need to know about cats, from choosing a kitten or cat and day-to-day advice on nutrition and grooming, to guidance on behavior, play, and health and diseases, Complete Cat Care will help readers provide the best possible care for a cat at every stage of its life."--Publisher's description.